From paths to stars - A. F. Alameddine (International Journal of Mathematics and Mathematical Sciences)
The number of cycles in the complement T′ of a tree T is known to increase with the diameter of the tree. A similar question is raised and settled for the number of complete subgraphs in T′ for a special class of trees via Fibonacci numbers. A structural characterization of extremal trees is also presented.